Entrepreneurial Practices of Fishing Ponds Examined from the Perspective of Maqasid Shariah in the City of Padangsidimpuan - Hidayat, Rahmat; Siregar, Ibrahim; Harahap, Darwis (Universitas Muhammadiyah Surabaya, 2024)
This research is motivated by the Shariah fishing system in the city of Padangsidimpuan. The contracts used in these fishing ponds are either buying and selling fish objects, or using leasing contracts with a bonus of fish. This study aims to understand the Maqasid Shariah perspective on Shariah fishing contracts in Padangsidimpuan regarding the status of payment for entrance tickets to Shariah fishing ponds in the city. This research is descriptive qualitative research, and the primary data sources used are the owners of fishing ponds and the local community engaged in fishing. Data collection techniques include interviews, observations, and documentation. After conducting the research, it was found that in terms of fiqh muamalah, the implementation of leasing fishing ponds is in accordance with the principles because the conditions and requirements of the lease have been fulfilled, and there are no issues between the pond owners and the fishermen in terms of transactions as both parties engage willingly. From the perspective of Maqasid Shariah, which serves as a benchmark for determining the goodness or badness (benefits and harms) of something, it is based on what constitutes basic human needs. In terms of Shariah economics, it is evident that someone entrusted as a lessor in this cooperation must act honestly towards the party leasing the fishing pond.